A Triptych of Bottomless Light: Repetition, Identity and Transcendence in Vladimir Nabokov’s Pale Fire - Eklund, Erik (2023)
Traversing philosophical theology and literary studies, this thesis proposes new avenues for considering the relevance and value of ‘non-identical repetition’ for delineating a poetics of authorial presence in Vladimir Nabokov’s Pale Fire. It argues that Nabokov distils the varieties of metaliterary and metaphysical experimentation typical of his lifelong project into a distinctly religious philosophical conversation about the varieties of mimesis in art and life and their relation to a transcendent, non-finite origin. This thesis begins by establishing Nabokov’s relationship to Christianity, which serves to demonstrate that his work, especially Pale Fire, is amenable to meaningful theological reflection. Turning to Pale Fire explicitly, it explores the history of the debate surrounding this novel’s authorial enigmas, attending especially to the way these theories respond to the dialectic of repetition and identity in the novel. From this analysis, this thesis suggests an innovative reading of Pale Fire. This approach obfuscates the conventional dichotomy of origin and copy, and therefore does not require the reader to choose between poem and commentary and their respective authors, as the relation between the two texts is not one of mimetic violence, but, rather, of peaceable, non-identical expression. That is, each is equally original because each is equally copy. An investigation into the theological underpinning of the (meta)literary issues which Pale Fire raises and examines uncovers new theological subtexts which indicate the distinctly theological contours of this novel’s textual performance of repetition, identity and transcendence. Finally, these subtexts are brought to bear on the question of authorial presence in Pale Fire, suggesting that its author is ‘in’ the text only as non-identical repetition, that is, as sign. It argues that this sign must be neither one nor many, but the two together, in order to accommodate the radical reciprocity of sameness and difference across poem and commentary.